Pengembangan Subject Specific Pedagogy PAI Berbasis Teams Games Tournament Family 100 terhadap Keaktifan Siswa di SMA N 1 Purbalingga - Arjun Fiqar Riyu, Wisnu; Harisatunnisa, Harisatunnisa (Jurnal Pendidikan Agama Islam, 2025)
As time progresses, students' needs increase. The use of technology and the internet in learning continues to generate innovation. However, in Islamic Religious Education subjects at SMA N 1 Purbalingga, they are often delivered with conventional practices. One indicator of successful learning is student activity. Teachers who only become the center of learning without paying attention to the passive conditions of students will hinder the occurrence of a lively dialogue of knowledge transfer. This study aims to develop a learning product in the form of Subject Specific Pedagogy Islamic Religious Education (PAI) based on the Teams Games Tournament Family 100 model to increase student activity. This study uses the Research and Development research method by adapting the ADDIE model which includes the following stages: Analysis, Design, Development, Implementation, and Evaluation. The development resulted in a SSP in the form of a TGT Family 100 teaching module and interactive media using Ms. PowerPoint equipped with action button features, animation, and audio to support game activities. The product was validated by material experts, media experts, and student activity experts. The validation results from the experts indicate that the developed SSP is in the "very good" category. Student responses also demonstrated that this research and development increased engagement, enthusiasm, and ease of understanding of Islamic Religious Education (PAI) Therefore, this media has proven effective and can be used as an innovative alternative in Islamic Religious Education (PAI).